An empirical investigation on sustainability of balancing item in Asian countries - Evan, Lau; Tuck Cheong, Tang (Routledge, 2008)
This study explores the sustainability of the balancing item in Asian economies. The conventional unit root tests (includes panel tests) illustrate that the results are rather inconclusive. However, the results from the series-specific panel unit root test consistently illustrate that five of the countries (Singapore, Bangladesh, Indonesia, Korea and Malaysia) balancing item is on the sustainable path. For other remaining eight countries (Maldives, Mongolia, Myanmar, Nepal, Pakistan, the Philippines, Sri Lanka and Thailand), there is evidence that her balancing item of balance of payments accounts is unsustainable.